2020
DOI: 10.1021/acsami.0c11715
|View full text |Cite
|
Sign up to set email alerts
|

MXene-Coated Air-Permeable Pressure-Sensing Fabric for Smart Wear

Abstract: Considering the fast development of wearable electronics and soft robotics, pressure sensors with high sensitivity, durability, and washability are of great importance. However, the surface modification of fabrics with high-sensitivity active materials requires that issues associated with poor interface adhesion and stability are resolved. In this study, we explored the key factors for firmly bonding MXene to fabric substrates to fabricate wearable and washable pressure sensing fabric. The interactions between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 52 publications
0
113
0
Order By: Relevance
“…The sensitivity of our sensor is higher than that of the pristine MXene film (Figure S5, Supporting Information) and the previously reported MXene‐based sensor (Figure 3f) and Table S1 (Supporting Information). [ 17,35–43 ] We further attempted to monitor the sensor in a lower pressure range. As shown in Figure S6a (Supporting Information), the flexible sensor creates accurate differentiation for different pressures within the pressure range of 0–61 Pa, and a good linear relationship is maintained for the I – V curves.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of our sensor is higher than that of the pristine MXene film (Figure S5, Supporting Information) and the previously reported MXene‐based sensor (Figure 3f) and Table S1 (Supporting Information). [ 17,35–43 ] We further attempted to monitor the sensor in a lower pressure range. As shown in Figure S6a (Supporting Information), the flexible sensor creates accurate differentiation for different pressures within the pressure range of 0–61 Pa, and a good linear relationship is maintained for the I – V curves.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that only a very small amount of the MXene fakes dropped off from the MCF during the sonication, confirming the strong adhesion between MXene and cotton fiber. Such a good stability is because that the ‐OH group on the surface of MXene could form covalent bonds with the N−O group of cotton fiber to induce a strong interface adhesion [11c] . Moreover, the Ti atoms on MXene would also bond with the N atoms on cotton to create Ti−N bonding, which furtherly contributes to the strong adhesion between MXene flakes and cotton fiber.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the reported studies, in general MXene has been fully demonstrated the feasibility and practical applicability for wearable intelligent fabric by simple, efficient, and low‐cost method, affording great value for the study of MXene on the next generation of portable, wearable textile‐based electronic devices for human motion monitoring. [ 178 ] However, MXene naturally oxidizes easily in aerobic and aqueous environments, the durability of MXene‐based textile sensor needs to be further studied in future research.…”
Section: D Mxene Composite Sensors For Multifunctional Sensorsmentioning
confidence: 99%
“…m) MXene tools pressure detection (single-region and multiregion) and 3D simulation diagrams of pressure-sensitive data. Reproduced with permission [178]. Copyright 2020, American Chemical Society.…”
mentioning
confidence: 99%